2020
DOI: 10.2147/ott.s242073
|View full text |Cite
|
Sign up to set email alerts
|

<p>LINC01272 Promotes Migration and Invasion of Gastric Cancer Cells via EMT</p>

Abstract: Purpose: Gastric cancer (GC) is the fifth most common tumor in the world, and most patients with GC have a poor prognosis. This study aimed to explore the biological influence and mechanism of LINC01272 in GC. Materials and Methods: Using bioinformatic analyses, we investigated the expression of LINC01272 in TCGA database and predicted the biological functions and mechanism of LINC01272 in GC. Then, we detected the expression of LINC01272 in GC cell lines, GC tissues, and corresponding normal tissues using rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Studies have shown that the EMT is closely related to the high invasion and metastasis of carcinoma cells [ 22 , 23 ]. An increasing amount of evidence has revealed that lncRNAs participate in the occurrence and progression of carcinoma by regulating the EMT of carcinoma cells, play the role of oncogene promoters or tumour suppressors and become key regulators of the migration, invasion and metastasis of tumour cells [ 24 ]. After downregulating and silencing lncTM4SF1-AS1, the expression levels of the E-cadherin protein, a marker protein of epithelial properties, were significantly increased, while the levels of N-cadherin, Snail and Twist 1 protein related to mesothelial properties were significantly decreased during the EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the EMT is closely related to the high invasion and metastasis of carcinoma cells [ 22 , 23 ]. An increasing amount of evidence has revealed that lncRNAs participate in the occurrence and progression of carcinoma by regulating the EMT of carcinoma cells, play the role of oncogene promoters or tumour suppressors and become key regulators of the migration, invasion and metastasis of tumour cells [ 24 ]. After downregulating and silencing lncTM4SF1-AS1, the expression levels of the E-cadherin protein, a marker protein of epithelial properties, were significantly increased, while the levels of N-cadherin, Snail and Twist 1 protein related to mesothelial properties were significantly decreased during the EMT.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01116 has been studied as an oncogene in many tumors, such as LAUD, its overexpression promotes LAUD proliferation and metastasis [53], contributes to ge tinib resistance in NSCLS through regulating IFI44 [54], results in resistance of LAUD to cisplatin via the EMT process [55]. Leng X et al indicated that SMIM25 (Aliases LINC01272) promoted gastric cancer metastasis through regulating EMT process [56]. The remaining lncRNAs have not seen relevant reports in previous studies, which are worthy of further research.…”
Section: Discussionmentioning
confidence: 99%
“…The SMIM25, also known as LINC01272, was upregulated gastric cancer (GC), and the over-expression of SMIM25 promoted the migration and invasion ability of GC cells by activating the epithelial-mesenchymal transition (EMT) process. 26 The EMT defines a process by which epithelial cells lose their cell polarity and cell-to-cell adhesion and acquire the migratory and invasive properties to become mesenchymal cells. 27 These changes are supposed to contribute to the establishment of endometriotic lesions in Ems.…”
Section: Discussionmentioning
confidence: 99%